The relationship between psychopathy and sexual sadism: a mixed-methods study - Papagathonikou, Theodoros (The journal of forensic psychiatry & psychology, 2025)
Psychopathy and sexual sadism are amongst the most controversial concepts of our times. The two forensically related constructs have often been associated at a theoretical and a clinical level. Very few studies, however, have sought to empirically assess the relationship between sexual sadism and psychopathy, and even fewer have explored the function of sadistic aggression within the construct of psychopathy. The current study followed a mixed-method design involving paper-based questionnaires, behavioural scales, and a semi-structured interview. Based on a sample of 59 forensic mental health patients and prisoners with a mean age of 41.01 years (SD = 10.30), the results indicate that psychopathy is significantly associated with both sexual sadism and trait sadism. Sexual sadists achieved higher psychopathy scores when compared to non-sexual sadists. Thematic analysis revealed differences in the function of aggression between sadistic and non-sadistic psychopaths. Three themes were identified: (a) The function of aggression, (b) Predatory fantasies, and (c) Victim – perpetrator dynamics. The findings of the study appear to support the hypothesis of the existence of sadistic psychopathy as a distinct subtype of the psychopathic disorder.